An Analysis of Ellipsis as a Translation Strategy Found in Pramoedya Ananta Toer’s Novel This Earth of Mankind (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates the use of ellipsis as a translation strategy in the English translation of the novel This Earth of Mankind by Pramoedya Ananta Toer. The research aims to identify the types of ellipsis and examine how ellipsis is realized as a translation strategy in the target text. This study employs a qualitative descriptive method by comparing the Indonesian source text with its English translation. The analysis is based on the ellipsis framework proposed by M.A.K. Halliday and Ruqaiya Hasan and the translation techniques proposed by Molina and Albir, as well as translation principles by Peter Newmark. A total of 135 instances of ellipsis were identified in the analyzed data. The findings reveal that three types of ellipsis occur in the translation, namely clausal, verbal, and nominal ellipsis, with clausal ellipsis appearing as the most dominant type. In terms of translation techniques, reduction is the most frequently applied strategy, indicating that the translator tends to condense recoverable linguistic elements rather than completely deleting them. The findings also show that communicative translation is the dominant translation principle, emphasizing readability and naturalness in the target language. These results suggest that ellipsis functions as an important strategy for achieving textual cohesion, narrative efficiency, and stylistic naturalness in literary translation.
Keywords: Ellipsis; Translation Strategy; Literary Translation; Communicative Translation; Textual Cohesion